Human immune responses elicited by an intranasal inactivated H5 influenza vaccine. (29th March 2020) - Ainai, Akira; van Riet, Elly; Ito, Ryo; Ikeda, Kazuyuki; Senchi, Kyosuke; Suzuki, Tadaki; Tamura, Shin‐ichi; Asanuma, Hideki; Odagiri, Takato; Tashiro, Masato; Kurata, Takeshi; Multihartina, Pretty; et al.
Abstract: Intranasally administered influenza vaccines could be more effective than injected vaccines, because intranasal vaccination can induce virus‐specific immunoglobulin A (IgA) antibodies in the upper respiratory tract, which is the initial site of infection. In this study, immune responses elicited by an intranasal inactivated vaccine of influenza A(H5N1) virus were evaluated in healthy individuals naive for influenza A(H5N1) virus. Three doses of intranasal inactivated whole‐virion H5 influenza vaccine induced strong neutralizing nasal IgA and serum IgG antibodies. In addition, a mucoadhesive excipient, carboxy vinyl polymer, had a notable impact on the induction of nasal IgA antibody responses but not on serum IgG antibody responses. The nasal hemagglutinin (HA)‐specific IgA antibody responses clearly correlated with mucosal neutralizing antibody responses, indicating that measurement of nasal HA‐specific IgA titers could be used as a surrogate for the mucosal antibody response. Furthermore, increased numbers of plasma cells and vaccine antigen‐specific Th cells in the peripheral blood were observed after vaccination, suggesting that peripheral blood biomarkers may also be used to evaluate the intranasal vaccine‐induced immune response. However, peripheral blood immune cell responses correlated with neutralizing antibody titers in serum samples but not in nasal wash samples. Thus, analysis of the peripheral blood immune response could be a surrogate for the systemic immune response to intranasal vaccination but not for the mucosal immune response. The current study suggests the clinical potential of intranasal inactivated vaccines against influenza A(H5N1) viruses and highlights the need to develop novel means to evaluate intranasal vaccine‐induced mucosal immune responses.